An anatomical variant of the posterior branch of the great auricular nerve: A case report and a short review of the literature (Indian Journal of Case Reports, 2024)
The great auricular nerve (GAN) is a sensory cutaneous nerve, which provides sensory innervation to the skin overlaying auricle, parotid gland, and mastoid region. The emergency of GAN is located at Erb’s point over the posterior burden of the belly of the sternocleidomastoid muscle (SCM). During its course, it normally bifurcates in a pair of, respectively, posterior and anterior, branches. The latter one then further divides into superficial and deep branches. Some different anatomical patterns of GAN branches were reported in the literature to underline the high variability of the GAN course. The aim of this case report is to underline a particular anatomical variant of a posterior branch of GAN we recently observed. It was characterized by an anomalous bifurcation involving two different groups of fibers, within the same field of innervation, which had an independent course toward the auricular lobe. To promptly face such a somewhat unexpected anomaly, besides the basic recommendation to surgeons of mastering a good knowledge of the high variability of the anatomy of GAN, a careful dissection around the SCM is believed to help the surgeon to recognize other anatomical variants of GAN course with the aim to preserve it.